Physicochemical and Organoleptic Characteristics of Functional Cookies Based On Brown Rice Flour and Moringa Leaf for Diabetes Mellitus - Nuzul 'Ainunni'mah; Nur Lailatul Muhlishoh; Aan Sofyan (Journal of Food and Agricultural Product, 2026)
Diabetes mellitus is a degenerative disease that requires dietary regulation throught the comsuption of complex carbohydrates with a low glycemic index and high fiber. This study aimed to develop functional cookies as a supplementary food based on local foods, are brown rice flour, moringa lead flour, and purple sweet potato. This study used experimental design with three cookie formulations, assesing moisture content and color. Furthermore, sensory (organoleptic) evaluation was conducted using 15 semi-trained panelists. Data were analyzed using ANOVA followed by Duncan Multiple Range Test. The results showed that there were significant differences (p<0.05) in aroma, taste, and overal acceptability. The formulation without moringa leaf flour, formulated with brown rice flour (130g) and puple sweet potato (25g), showed the highest sensory acceptance, based on the parameters of taste, aroma, color, texture, and overall evaluation of the product. The water content test showed that all three formulas exceeded the SNI 2973-2011 (< 5%) with the highest values in formula 1 with moringa leaf flour (10g), brown rice flour (140g), and purple sweet potato (50g). The colour content test showed that formula 3 without moringa leaf flour, formulated with brown rice flour (130g) and puple sweet potato (25g) had the highest brightness level (L*). All three cookies formulas were dominated by red based on the a* value, and tended to be yellow accorded to the b* value. Therefore, formula 3 without moringa leaf flour was the most organoleptically accepted, although moisture content improvement is required. Keywords: diabetes mellitus, brown rice flour, moringa lead flour, dietatary fiber, glycemic index